Direct molecular analysis of myotonic dystrophy in the German population: important considerations in genetic counselling. Issue 8 (August 1995) - Meiner, A; Wolf, C; Carey, N; Okitsu, A; Johnson, K; Shelbourne, P; Kunath, B; Sauermann, W; Thiele, H; Kupferling, P
Abstract : Myotonic dystrophy (DM) is associated with the expansion and instability of a trinucleotide (CTG) repeat at the DM locus on chromosome 19. Direct genomic analysis in the German population was carried out on 18 DM families, six families with equivocal diagnosis, 69 subjects with equivocal clinical diagnosis, and 100 controls using the polymerase chain reaction (PCR) and a refined Southern protocol. In the majority of the cases molecular analysis confirmed the clinical diagnosis. These included seven cases of congenital DM (CDM) with widely differing gene expansions and instabilities. In most DM families the expanded fragment became larger in successive generations, but we also identified four families with contractions and two families that showed stability of the enlarged fragment during transmission. In four clinically defined DM patients we were unable to detect enlarged CTG repeats. Sequencing of each exon of the DM gene in two of these patients failed to show any mutations. Our cases have important implications for genetic counselling of DM families, highlighting both the diagnostic value of direct genomic analysis and its limitations.